The spy with the red balloon - Locke, Katherine (Locke, Katherine. Balloonmakers duology., 2019)
Siblings Ilse and Wolf Klein are blackmailed into using their magic to help the Allies during WWII. While Ilse aids the Americans with their atomic bomb, Wolf is in Germany trying to sabotage Hiltler's nuclear program. But Wolf's mission is compromised, and he'll need Ilse to save him before it's too late.